2012
DOI: 10.1371/journal.pone.0032004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity and Nuclear Localization of Cabut, the Drosophila Ortholog of Vertebrate TGF-β-Inducible Early-Response Gene (TIEG) Proteins

Abstract: BackgroundCabut (Cbt) is a C2H2-class zinc finger transcription factor involved in embryonic dorsal closure, epithelial regeneration and other developmental processes in Drosophila melanogaster. Cbt orthologs have been identified in other Drosophila species and insects as well as in vertebrates. Indeed, Cbt is the Drosophila ortholog of the group of vertebrate proteins encoded by the TGF-ß-inducible early-response genes (TIEGs), which belong to Sp1-like/Krüppel-like family of transcription factors. Several fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 104 publications
6
30
1
Order By: Relevance
“…Gene Ontology (GO) analysis indicated that this subset of genes was enriched in transcriptional activity, cell migration, mitotic cell cycle and signaling pathways known to play a role in imaginal disk development (Supplementary Fig S1B). As expected, among Cbt targets we found previously described genes such as salm ( spalt major ) or cbt itself , but also several unidentified target genes such as wg ( wingless ) or vg ( vestigial ) (Fig B).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Gene Ontology (GO) analysis indicated that this subset of genes was enriched in transcriptional activity, cell migration, mitotic cell cycle and signaling pathways known to play a role in imaginal disk development (Supplementary Fig S1B). As expected, among Cbt targets we found previously described genes such as salm ( spalt major ) or cbt itself , but also several unidentified target genes such as wg ( wingless ) or vg ( vestigial ) (Fig B).…”
Section: Resultssupporting
confidence: 85%
“…Control samples (mock) of GFP À Marina Ruiz-Romero et al Cabut/dTIEG is a Yorkie partner for growth control EMBO reports subset of genes was enriched in transcriptional activity, cell migration, mitotic cell cycle and signaling pathways known to play a role in imaginal disk development ( Supplementary Fig S1B). As expected, among Cbt targets we found previously described genes such as salm (spalt major) or cbt itself [11,17], but also several unidentified target genes such as wg (wingless) or vg (vestigial) ( Fig 1B). Cbt association around the TSS may be an indication of its function as a primary regulatory element, but does not provide any information about its role as an activator or a repressor.…”
Section: Widespread Occupancy Of Cbt On Chromatinsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, select functions of some of these proteins (such as KLF11 and KLF14) can cause common human metabolic diseases, including neonatal and juvenile diabetes, as well as the obesity-insulin resistance-metabolic syndrome, which leads to adult type 2 diabetes (10,16,17). Thus, because of their structural conservation and function, these six proteins have become to be known as the Cabut family of metabolic regulators (9,18). Consequently, we and others have recently focused on how these proteins regulate the expression of genes and gene networks involved in lipid metabolism and signaling.…”
mentioning
confidence: 99%